Assessment of Chromosomal Damage and Apoptosis in Exfoliated Buccal Cells of Potentially Malignant Disorders and Oral Cancer (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: exfoliative buccal cells; micronucleated cells; apoptosis; potentially malignant disorders; oral cancer